Amelioration of right ventricular systolic function and stiffness in a patient with idiopathic pulmonary arterial hypertension treated with oral triple combination therapy. (March 2018) - Nakaya, Toshitaka; Tsujino, Ichizo; Ohira, Hiroshi; Sato, Takahiro; Watanabe, Taku; Oyama-Manabe, Noriko; Nishimura, Masaharu
Right ventricular (RV) function is an important determinant of the prognosis in patients with pulmonary arterial hypertension (PAH). In the context of recent therapeutic progress, there is an increasing need for better monitoring of RV function for management of PAH. We present the case of a 42-year-old woman with idiopathic PAH who was treated with three oral pulmonary vasodilators, i.e. tadalafil, ambrisentan, and beraprost. At the baseline assessment, the mean pulmonary arterial pressure (mPAP) was 45 mmHg, cardiac index (CI) was 1.36 L/min/m 2, and pulmonary vascular resistance (PVR) was elevated to 21.3 Wood units (WU). However, three months after the start of combination treatment, mPAP and PVR decreased to 42 mmHg and 7.5 WU, respectively, and conventional indices of RV function, such as CI, right atrial area, and right atrial pressure also improved. Beyond three months, however, there were no further improvements in mPAP, PVR, or indices of RV function. In addition, we calculated three recently introduced indices of intrinsic RV function: end-systolic elastance (Ees; an index of RV contractility), Ees/arterial elastance ratio (Ees/Ea; an index of RV/pulmonary arterial coupling), and β (an index of RV stiffness) using cardiac magnetic resonance imaging and Swan-Ganz catheterization measurements. Notably, in contrast to conventional parameters, Ees, Ees/Ea, and β showed persistent improvement during the entire two-year follow-up. The application of Ees, Ees/Ea, and β may play an additional role in a comprehensive assessment of RV function in PAH.